UNEVEN DEVELOPMENT IN GROWTH MODELS OF KEYNESIAN INSPIRATION - Oreiro, José Luis; Dotta, Vitor; Heringer Machado, João Pedro (Práticas de Administração Pública, 2022)
This article aims to make a systematic presentation of Keynesian-inspired growth models (Neo-Keynesian and Kaldorian Models), focusing on the role of aggregate demand in the analysis of the determinants of uneven development, which means that the focus of the article will be the proximate causes of economic growth in Maddison´s sense (1988) from the perspective of Keynesian Economics. These growth models will be classified into two groups, namely: growth models with limited labor supply, more directly applicable to mature economies; and growth models led by aggregate demand, in which labor supply can be regarded as unlimited or perfectly elastic, thus being more applicable to the case of dual economies in Lewis's sense or in the process of Industrialization. In the case of models with limited supply of labor, the growth rate compatible with a balanced growth path is determined by the natural growth rate, consisting of the sum between the growth of the workforce and the growth of labor productivity. As technological progress is largely embedded in new machinery and equipment, the pace of growth of labor productivity depends critically on the pace of capital accumulation; but the extent to which technical progress is incorporated into the economy depends on the level of the technological gap, which expresses the technological asymmetries between the various economies. In this setting, different levels of technological gap are compatible with different rates of growth of labor productivity along the balanced growth trajectory, thus generating divergences between the growth rates of the countries.